SANKSI DALAM KETERLAMBATAN PEMBAYARAN PAJAK (REKLAME, KENDARAAN, RESTORAN) - Hutabarat, Dany Try Hutama; Simanjuntak, Angelina Deasyta; Putra, Aulia; Paramitha, Jihan; Panjaitan, Khairunnisak; Stefany, Nandika Tiara Puteri; Surbakti, Febby Andriana; Diana, Sri; Akmal, Nurul (Nusantara Hasana Journal, 2022)
In the context of financing development, the role and potential of the taxation sector is very large, especially to support the success of regional development and national development. Sources of state financing include taxes and natural resources. The purpose of this study is to determine the sanctions for late payments as well as affecting the Regional Original Income (PAD) in vehicle taxes, restaurant taxes or advertisement taxes. Techniques in research using qualitative methods and literature study. The results of this study indicate that every increase in the imposition of tax sanctions will reduce taxpayer compliance in paying taxes and taxpayer awareness, service quality, tax audits and positive tax taxes on taxpayer compliance.